Risk Factors for Postoperative Intra-Abdominal Abscess in Pediatric Perforated Appendicitis Following Laparoscopic Appendectomy: A Multicenter Analysis - Joonhyuk Son; Ji-Won Han; Chaeyoun Oh (Children)
Background: Perforated appendicitis in children is a frequently encountered and significant surgical condition. The treatment of choice is laparoscopic appendectomy, but this carries a risk of postoperative intra-abdominal abscess (IAA). The purpose of this study was to determine risk factors linked to the occurrence of IAA following laparoscopic surgery in pediatric perforated appendicitis. Methods: This retrospective cohort study analyzed 137 children with perforated appendicitis who received laparoscopic appendectomy at four tertiary hospitals between March 2018 and December 2022. Data on patient demographics, preoperative clinical characteristics, and surgical details were collected. Independent risk factors for IAA formation were determined using logistic regression analysis. Results: The overall incidence of postoperative IAA was 10.9%. Prolonged symptom duration and elevated CRP levels were associated with higher IAA rates. Patients who developed IAAs experienced prolonged postoperative fevers and longer hospital stays. Significant risk factors for IAA identified through multivariable analysis included a higher severity grade of appendicitis (≥Grade IV, OR 5.9, p = 0.034) and the presence of a free appendicolith during surgery (OR 5.549, p = 0.01). Of the patients who developed IAAs, nine (60%) improved with conservative treatment, while six (40%) required invasive procedures. Conclusions: A higher severity grade of appendicitis (≥Grade IV) and the presence of a free appendicolith are significant predictors of postoperative IAAs in pediatric perforated appendicitis. Recognizing these factors can help guide clinical management and postoperative care, potentially reducing the incidence of this complication.